Randomised phase III study of S-1 alone versus S-1 plus lentinan for unresectable or recurrent gastric cancer (JFMC36-0701). (September 2016) - Yoshino, Shigefumi; Nishikawa, Kazuhiro; Morita, Satoshi; Takahashi, Tsuyoshi; Sakata, Koichiro; Nagao, Jiro; Nemoto, Hiroshi; Murakami, Nozomu; Matsuda, Takeru; Hasegawa, Hiroyasu; Shimizu, Ryoichi; Yoshikawa, Takaki; et al.
Abstract: Background: Lentinan (LNT) is a purified β-1, 3-glucan that augments immune responses. The present study was conducted to assess the efficacy of LNT in combination with S-1 as a first-line treatment for unresectable or recurrent gastric cancer. Patients and methods: Eligible patients were randomly assigned to receive S-1 alone or S-1 plus LNT. The primary end-point was overall survival (OS). Secondary end-points were time-to-treatment failure (TTF), overall response rate (ORR), safety, quality of life (QOL), and biomarker. The percentages of LNT-binding monocytes in peripheral blood prior to treatment were analysed for the biomarker assessment. Results: One hundred and fifty-four and 155 patients were randomly assigned to receive S-1 alone or S-1 plus LNT, respectively. The median OS was 13.8 and 9.9 months ( P  = 0.208), the median TTF was 4.3 and 2.6 months ( P  < 0.001), the ORR was 22.3% and 18.7% for the S-1 and S-1 plus LNT groups, respectively. The incidences of haematologic and non-haematologic adverse events were similar, and no significant changes in QOL scores were observed during the treatment in both groups. In a subpopulation of patients with LNT-binding monocytes ≥2%, patients who received more than two cycles of chemotherapy showed a longer survival time in the S-1 plus LNT group. Conclusions: OS did not improve and TTF was significantly worse in the S-1 plus LNT group as compared with the S-1-only group. This study showed no efficacy of LNT when combined with S-1 treatment in patients with unresectable or recurrent gastric cancer. Clinical trial registration ID number: UMIN 000000574. Highlights: Lentinan (LNT) is a purified β-1, 3-glucan and augments immune responses. A phase III study of S-1 versus S-1 plus LNT was conducted for advanced gastric cancer. This study showed no efficacy of LNT combined with S-1 treatment. LNT-binding monocytes were analysed for the biomarker assessment. In S-1 plus LNT group, long survivors were seen in subgroup of patients with a high percentage of LNT-binding monocytes.